2011
DOI: 10.1038/npp.2011.12
|View full text |Cite|
|
Sign up to set email alerts
|

Group II Metabotropic Glutamate Receptor Agonist Ameliorates MK801-Induced Dysfunction of NMDA Receptors via the Akt/GSK-3β Pathway in Adult Rat Prefrontal Cortex

Abstract: Pharmacological intervention targeting mGluRs has emerged as a potential treatment for schizophrenia, whereas the mechanisms involved remain elusive. We explored the antipsychotic effects of a mGluR2/3 agonist in the MK-801 model of schizophrenia in the rat prefrontal cortex. We found that the mGluR2/3 agonist LY379268 effectively recovered the disrupted expression of NMDA receptors induced by MK-801 administration. This effect was attributable to the direct regulatory action of LY379268 on NMDA receptors via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 111 publications
1
59
0
Order By: Relevance
“…Downregulated NMDAR subunits are usually seen in postmortem tissue from schizophrenics (Akbarian et al, 1996;Gao et al, 2000;Kristiansen et al, 2007) and animal models with disrupted NMDAR function that have SZ-like symptoms (Belforte et al, 2010;GunduzBruce, 2009;Lisman et al, 2008;Xi et al, 2011). However, the majority of these experiments has been conducted on postmortem adult human brains or in adult animals and thus does not exclude the possibility that NMDAR expression and function can be differentially regulated over development.…”
Section: Discussionmentioning
confidence: 94%
“…Downregulated NMDAR subunits are usually seen in postmortem tissue from schizophrenics (Akbarian et al, 1996;Gao et al, 2000;Kristiansen et al, 2007) and animal models with disrupted NMDAR function that have SZ-like symptoms (Belforte et al, 2010;GunduzBruce, 2009;Lisman et al, 2008;Xi et al, 2011). However, the majority of these experiments has been conducted on postmortem adult human brains or in adult animals and thus does not exclude the possibility that NMDAR expression and function can be differentially regulated over development.…”
Section: Discussionmentioning
confidence: 94%
“…Given the significant effects of mGluR2/3 agonists on NMDAR expression and function in the adult rat PFC (Xi et al, 2011; Li et al, 2015b), one of the major concerns of this undertaking was the potential side effects. However, LY39 did not have significant effects on the expression of NMDAR subunits and limited effects on NMDA-mEPSCs in saline-treated animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that compounds targeting mGluR2/3 are well-tolerated, exhibit few side-effects, and demonstrate a strong potential for alleviating cognitive impairments in both animal models and human subjects with SCZ (Helton et al, 1998; Spooren et al, 2002; Swanson et al, 2005; Fell et al, 2012; Harvey and Shahid, 2012). Specifically, activation of mGluR2/3 can decrease glutamate release pre-synaptically (Schoepp et al, 1999; Cartmell and Schoepp, 2000; Moghaddam, 2004), and simultaneously potentiate NMDAR function post-synaptically (Tyszkiewicz et al, 2004; Xi et al, 2011; Cheng et al, 2013; Trepanier et al, 2013; Wang et al, 2013; Li et al, 2015a; Li et al, 2015b; Engel et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The classification of age group [(newborns on postnatal day (P1) to P7, early juvenile at P14, late juvenile at P21 to P28, adolescence at P45 and young adult at P60] was based on others' (Spear, 2000) and our previous studies (Snyder et al, 2013;Wang and Gao, 2009). Whole cell extracts from medial PFC tissues were processed for Western blot analysis with different antibodies as indicated in our published procedure (Xi et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…There are two mammalian isoforms of GSK3, which are primarily regulated by inhibitory phosphorylation at either Ser21 of GSK3α or Ser 9 for GSK3β. Psychomimetic drugs increase GSK3β activity, whereas antipsychotics result in the inhibition of GSK3β by altering pGSK3βSer9 levels (Freyberg et al, 2010;Li et al, 2007;Xi et al, 2011). Synaptic GSK3β has been demonstrated to be important in synaptic plasticity regulation, and crosstalk between LTP and LTD (Peineau et al, 2007).…”
Section: Introductionmentioning
confidence: 98%